Discovery of N-(1-(3-(4-phenoxyphenyl)-1, 2, 4-oxadiazol-5-yl)ethyl)acetamides as novel acetyl-CoA carboxylase 2 (ACC2) inhibitors with peroxisome proliferator-activated receptor α/δ (PPARα/δ) dual agonistic activity. Issue 21 (1st November 2016) - Okazaki, Shogo; Noguchi-Yachide, Tomomi; Sakai, Taki; Ishikawa, Minoru; Makishima, Makoto; Hashimoto, Yuichi; Yamaguchi, Takao
Graphical abstract: Abstract: Acetyl-CoA carboxylases (ACCs) catalyze a critical step in de novo lipogenesis, and are considered as promising targets for treatment of obesity, dyslipidemia and type 2 diabetes mellitus. On the other hand, peroxisome proliferator-activated receptors (PPARs) are well-established therapeutic targets for these metabolic syndrome-related diseases. Therefore, we considered that dual modulators of ACC and PPARs would be promising candidates as therapeutic agents. Here, we designed a series of acetamides based on the molecular similarity between ACC inhibitors and PPAR agonists. Screening of the synthesized compounds identified N -(1-(3-(4-phenoxyphenyl)-1, 2, 4-oxadiazol-5-yl)ethyl)acetamides as novel ACC2 inhibitors with PPARα/PPARδ dual agonistic activity. Structure–activity relationship studies and further structural elaboration afforded compounds with distinct activity profiles. Our findings should be helpful for the discovery of candidate agents with an appropriate balance of ACC-inhibitory and PPAR-activating activities for therapeutic lipid control.